(untitled) (Ames, Iowa, 2007)
Published in Cooperation with THE UNITED STATES AQUACULTURE SOCIETY. As aquaculture production continues to grow and develop there is a continuous search for new species to culture to be able to fully exploit new national and international markets. Species selection for aquaculture development often poses an enormous challenge for decision makers who must decide which species and culture technologies to support with public resources, and then how best to divide those resources. Species and System Selection for Sustainable Aquaculture brings together contributions from international experts with experience in identifying potential species and production systems for sustainable aquaculture with a socioeconomic focus. The book is divided into three sections: Principles, Practices, and Species-Specific Public Policy for Sustainable Development. An outgrowth of a workshop held as part of the Aquaculture Interchange Program with examples from around the globe carefully edited by PingSun Leung, Pat O'Bryen, and Cheng-Sheng Lee this volume will be an important reference for all researchers, professionals, economists, and policy-makers involved in selecting new species for the development of sustainable aquaculture.
Keywords: Sustainable aquaculture.,Fishery management; Nuôi trồng thủy sản